Biocomposite materials based on polyethylene and amphiphilic polymer-iron metal complex - I. Yu. Vasilyev (Тонкие химические технологии, 2023)
Objectives. To obtain and study the properties including degradability of polymer composite materials (PCM) based on low-density polyethylene (LDPE) obtained by introducing an environmentally friendly additive comprising an oxo-decomposing additive (ODA) based on an amphiphilic polymer-iron metal complex, which accelerates the process of polymer degradation.Methods. PCMs based on LDPE and ODA were produced by processing in laboratory extruders in the form of strands, granules, and films. Thermodynamic properties were determined by differential scanning calorimetry in the temperature range 20-130 °C. In order to assess the performance characteristics (physical and mechanical properties) of the PCM, tensile strength and elongation at break were determined. The biodegradability of PCM was evaluated by Sturm's method, with the biodegradation index being determined by the amount of CO2 gas released as a result of microorganism activity, as well as composting by placing the PCMs for six months in biohumus. Changes in physical and mechanical properties and water absorption of the films during storage were evaluated. The photochemical degradability of the PCM was determined by exposing it to ultraviolet radiation for 100 h (equivalent to approximately one year of exposure of the films under natural conditions). The appearance of the composite samples following removal from the biohumus was determined using an optical microscope with ×50 magnification in transmitted and reflected light.Results. Following biodegradation by composting, the physical and mechanical properties of PCMs decrease by an average of 40.6%. This is related to the structural changes that occur in composites during storage in biohumus, i.e., the formation of a looser structure due to the development of large clusters of microorganisms that affect the formation of microcracks. It leads to the stage of fragmentation of the polyethylene matrix and indicates the progress of biological degradation of composites. In this case, the water absorption of the composite samples was 63% after 96 h of exposure. The biodegradability index determined by the Sturm method after 28 days of bubbling had changed by 82%, indicating an intensive biodegradation process. Exposure to ultraviolet radiation for 96 h resulted in the complete destruction of the PCMs, which turned into small “flakes.” This method is the most effective for the degradation of LDPE- and ODA-based PCMs.Conclusions. According to the results of the study of ODA-containing PCMs based on an amphiphilic polymer-iron metal complex, the tested filler-modifier can be recommended for the production of PCMs offering an accelerated degradation period.